Educational Policy in the United States: Context of Current Debates; Impact in Latin America - Pini, Mónica Eva (Education Policy Analysis Archives, 2000)
The objective of this article is to analyze some of the most relevant debates about current educational policies in the United States, and to explore the universalility of some of the ideas and strategies which have already been put in place in Latin America. The policies I will discuss are Goals 2000 and school choice proposals, especially those of charter schools and vouchers. These policies question the key definitions of educational goals, the role of the state, and democratic values. Through the analysis of different documents, reports, and research studies, the political context from which they emerged, and a critical perspective, discourses and policies are interpreted. The market model and the strong forces behind many of these proposals makes it necessary for us to think about how these ideas affect the social distribution of education and democratic ideals, both in the United States and in Latin America.